BIPLOT ANALYSIS OF SILICON DIOXIDE ON EARLY GROWTH OF SUNFLOWER - Sabaghnia, Naser; Janmohammadi, Mohsen (Plant Breeding and Seed Science, 2016)
Research into nanotechnology has advanced in almost all fields of technology and the aim of this study was to evaluate the role of nano-silicon dioxide (nano-SiO2) in germination performance sunflower. Germination and seedling growth are the most important stage of plant development and are critical factors to crop production and are essential to achieve optimum performance. The effects of pre-germination hydration in solutions of nano-SiO2 (0, 0.2, 0.4, 0.6, 0.8, 1 and 1.2 mM for 8 h) on germination characteristics of sunflower were investigated. The trait by treatment (TT) biplot explained 93% of the total variation of the standardized data (77% and 16% for the first and second principal components, respectively). According to polygon-view of TT biplot, T2 (0.2 mM) had the highest values for all of the measured traits except mean germination time and the time to 50% germination. The germination percentage was determined as the best trait and showed the high association with promptness index, energy of germination and germination rate traits. The results of the present study indicated that pre-sowing seed treatments with low concentration of nano-SiO2 had favorable effect sunflower seed germination and seedling early growth. Such a similar outcome could be applied in the future to outline other crops in response to nano-particles as well as to help define tolerance tools for recommendations in stressful conditions in the world.